2023
DOI: 10.3390/cancers15092630
|View full text |Cite
|
Sign up to set email alerts
|

The Uncomfortable Truth: Open Thoracotomy versus Minimally Invasive Surgery in Lung Cancer: A Systematic Review and Meta-Analysis

Abstract: For decades, lung surgery in thoracic cancer has evolved in two ways: saving more parenchyma and being minimally invasive. Saving parenchyma is a fundamental principle of surgery. However, minimally invasive surgery (MIS) is a matter of approach, so it has to do with advances in surgical techniques and tools. For example, MIS has become possible with the introduction of VATS (video-assisted thoracic surgery), and the development of tools has extended the indication of MIS. Especially, RATS (robot-assisted thor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A meta-analysis of seven RCTs found that VATS and thoracotomy did not differ in terms of operating time or early mortality [ 83 ]. However, hospital stay was slightly shorter in VATS compared with thoracotomy.…”
Section: Impact Of Surgical Access (Open and Mis (Vats And Rats)) On ...mentioning
confidence: 99%
“…A meta-analysis of seven RCTs found that VATS and thoracotomy did not differ in terms of operating time or early mortality [ 83 ]. However, hospital stay was slightly shorter in VATS compared with thoracotomy.…”
Section: Impact Of Surgical Access (Open and Mis (Vats And Rats)) On ...mentioning
confidence: 99%